Coping with the Unexpected: Patient Trust in Physicians following Delivery - Kole, Martha B.; Ayala, Nina K.; Clark, Melissa A.; Has, Phinnara; Werner, Erika F. (American Journal of Perinatology, 2020)
Objective Patient's trust in physicians is a significant predictor of continuity, adherence, and satisfaction with care. However, it is unclear what influences a woman's trust in her physician. This study sought to determine if women's trust in their clinicians was affected by unexpected outcomes at the time of delivery.Study Design This is a secondary analysis of a prospective cohort of 300 postpartum women with gestational diabetes mellitus. Participants completed the validated Trust in Physician Scale during their postpartum hospitalization. Participants' scores were compared based on their exposure to an unexpected pregnancy outcome.Results Of the 300 women consented to participate in this study, 294 completed the Trust in Physician Scale. The mean overall trust score was 80/100 with a range of 42 to 100. Unexpected pregnancy outcomes occurred in 41% (120) of women in this cohort. There was no significant difference in the trust score between women who did and did not have at least one unexpected outcome (0.79 vs. 0.79, p = 0.93). Additionally, there was no significant association between the trust score and any individual unexpected pregnancy outcome.Conclusion Unexpected pregnancy outcomes are not associated with changes in women's trust in their obstetric clinicians. These results emphasize the antepartum period as the essential time for patient–physician relationship building which has important implications for postpartum follow-up and long-term psychiatric sequelae from unexpected outcomes.
Keywords: patient–physician relationship; trust; unexpected pregnancy outcome; gestational diabetes